UCP1 Knockin Induces Lipid Dynamics and Transcriptional Programs in the Skeletal Muscles of Pigs - Xu, Ziye; Chen, Wentao; Wang, Liyi; You, Wenjing; Wang, Yanfang; Wang, Yizhen; Zhao, Jianguo; Shan, Tizhong (Frontiers in Cell and Developmental Biology, 2022)
Uncoupling protein 1 (UCP1), the hallmark protein responsible for nonshivering thermogenesis in adipose tissue (especially brown adipose tissue) has regained researchers’ attention in the context of metabolic disorders following the realization that UCP1 can be activated in adult humans and reconstituted in pigs. Both skeletal muscle and adipose tissue are highly dynamic tissues that interact at the metabolic and hormonal level in response to internal and external stress, and they coordinate in maintaining whole-body metabolic homeostasis. Here, we utilized lipidomics and transcriptomics to identify the altered lipid profiles and regulatory pathways in skeletal muscles from adipocyte-specific UCP1 knock-in (KI) pigs. UCP1 KI changed the contents of glycerophospholipids and acyl carnitines of skeletal muscles. Several metabolic regulatory pathways were more enriched in the UCP1 KI skeletal muscle. Comparison of the transcriptomes of adipose and skeletal muscle suggested that nervous system or chemokine signaling might account for the crosstalk between these two tissues in UCP1 KI pigs. Comparison of the lipid biomarkers from UCP1 KI pigs and other mammals suggested associations between UCP1 KI-induced metabolic alternations and metabolic and muscle dysfunction. Our study reveals the lipid dynamics and transcriptional programs in the skeletal muscle of UCP1 KI pigs and suggests that a network regulates metabolic homeostasis between skeletal muscle and adipose tissue.